2020
DOI: 10.1002/cam4.3498
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‐196a‐5p inhibits testicular germ cell tumor progression via NR6A1/E‐cadherin axis

Abstract: Testicular germ cell tumors (TGCTs) are a diverse group of neoplasms that are derived from dysfunctional fetal germ cells and can also present in extragonadal sites. The genetic drivers underlying malignant transformation of TGCTs have not been fully elucidated so far. The aim of the present study is to clarify the functional role and regulatory mechanism of miR‐196a‐5p in TGCTs. We demonstrated that miR‐196a‐5p was downregulated in TGCTs. It can inhibit the proliferation, migration, and invasion of testicular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that miR-196a, acts as an oncogene, exert multiple functions in carcinogenesis and cancer progression, such as down-regulation of miR-196a inhibited proliferation and invasion of hepatocellular carcinoma (HCC) cells by targeting FOXO1 [ 4 ]; in breast cancer, overexpression of miR-196a promotes tumor growth and metastasis by targeting SPRED1 [ 5 ]; in osteosarcoma, it could promote cell migration, invasion and the epithelial–mesenchymal transition by targeting HOXA5 [ 6 ]. Whereas, in testicular germ cell tumor, it was also reported to repress cell proliferation, migration, invasion and tumor neurogenesis by inhibition of NR6A1/E-cadherin signaling axis [ 7 ]. Moreover, in head and neck cancer, cancer-associated fibroblasts derived exosomal miR-196a was responsible for cisplatin resistance by targeting CDKN1B and ING5 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that miR-196a, acts as an oncogene, exert multiple functions in carcinogenesis and cancer progression, such as down-regulation of miR-196a inhibited proliferation and invasion of hepatocellular carcinoma (HCC) cells by targeting FOXO1 [ 4 ]; in breast cancer, overexpression of miR-196a promotes tumor growth and metastasis by targeting SPRED1 [ 5 ]; in osteosarcoma, it could promote cell migration, invasion and the epithelial–mesenchymal transition by targeting HOXA5 [ 6 ]. Whereas, in testicular germ cell tumor, it was also reported to repress cell proliferation, migration, invasion and tumor neurogenesis by inhibition of NR6A1/E-cadherin signaling axis [ 7 ]. Moreover, in head and neck cancer, cancer-associated fibroblasts derived exosomal miR-196a was responsible for cisplatin resistance by targeting CDKN1B and ING5 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ChIP experiments were performed according to the literature. 65 After transfection with siNC or siCHD2 for 48 h, C18-4 cells were cross-linked with 1% formaldehyde for 10 min at 37°C, terminated by 0.125 mol/L glycine at room temperature and then lysed by SDS lysis. Samples were sonicated at 30% power with a 5 s pulse and 5 s intervals at 4°C for 8 min using a Bioruptor Pico (Diagenode s.a., Seraing, Belgium) to obtain 200∼1000 bp fragments.…”
Section: Methodsmentioning
confidence: 99%
“…[ 35 ] By adding an appropriate amount of inorganic biomaterials, the ions can be released from the bioinks in a controlled manner. [ 36 ] Therefore, the ions released by inorganic biomaterials contribute to the gelation of the hydrogels and adjust the cross‐linking process, thereby improving the printing fidelity. Accordingly, kinds of inorganic biomaterials were added into the bioinks to modify the hydrogel for improving the printing fidelity.…”
Section: Inorganic Biomaterials Functionalized Bioinksmentioning
confidence: 99%